If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -3 + x = 12 Reorder the terms: -3 + 4x + x = 12 Combine like terms: 4x + x = 5x -3 + 5x = 12 Solving -3 + 5x = 12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 5x = 12 + 3 Combine like terms: -3 + 3 = 0 0 + 5x = 12 + 3 5x = 12 + 3 Combine like terms: 12 + 3 = 15 5x = 15 Divide each side by '5'. x = 3 Simplifying x = 3
| 7(2x+9)=3x+28 | | 4s-12=4s-12 | | 0=t^3-9t+2 | | 2.5(x-2)= | | 00.6(y-15)=0.06y+0.05 | | =-86(49+(-48)) | | 14x+56=16x+32 | | 5cosx+3cos(2x)=3 | | 2.5(x-2)=4x | | 0.14m+3-0.6m=0.28m-0.7 | | .04x+13(10000-x)= | | (1x^4-1y)dx+(-1x+4y^2)dy=0 | | 6x-8-4x=2x-8 | | log(x)+log(x-7)=log(18x) | | 0.45(50)+0.05c=0.15(50+c) | | 2y+14=-2(-y-2) | | 2a+5=1.5 | | 8x^2-2=14 | | 7x-20=9x-88 | | 8x^2=14 | | 9x+8=10x+10 | | =17(97)+17(3) | | 0.5x+2=22 | | -1/2(x-5)=1/5(x-5) | | 0.5+2=22 | | .05+45p=65 | | f(x)=-3x^2+8x+5 | | 11y^2-18y+7=0 | | 3(x+2)=4x-9 | | -6-3(y-2)=7(-5y+6)+3 | | 5x-12-x/-2 | | 6x+18y=72 |